Strategi Promosi dan Pengaruhnya terhadap Keputusan Pembelian Konsumen pada Toko Ice Cream Mixue Cikande Permai - Riki Gana Suyatna; Salma Az zahra; Neni Apriliyani; Nuryeni Nuryeni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid expansion of the food and beverage (F&B) industry in Indonesia has intensified competition among global franchises, including Mixue Ice Cream & Tea. Unlike previous studies that relied on quantitative surveys, this research adopts a qualitative descriptive approach to explore how promotional strategies influence consumer purchasing decisions at Mixue Cikande Permai. Data were collected through in-depth interviews with consumers, store management, and promotional staff, complemented by direct observation and documentation of promotional activities. To ensure validity, the study employed triangulation of sources, techniques, and time, allowing a comprehensive understanding of consumer perceptions and behaviors. The findings reveal that localized and interactive promotional strategies particularly social media campaigns, discount programs, and product bonuses are perceived as highly effective in shaping consumer interest and actual purchasing decisions. Consumers emphasized the psychological impact of bonus products and the persuasive nature of digital advertising, which foster both loyalty and repeat purchases. This study contributes to the literature by highlighting the importance of contextualized promotional efforts in suburban industrial areas, offering practical insights for franchise managers seeking to sustain competitiveness in Indonesia’s dynamic F&B market.